2008
DOI: 10.5483/bmbrep.2008.41.5.394
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic bent DNA colocalizes with the sequence involved in the Nd-sD mutation in the Bombyx mori fibroin light chain gene

Abstract: Multiple sequence alignments of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Sequence analysis showed that this intron has several conserved regions, mainly in the segment involved in the Nd-s D mutation in the fib-L gene. Recently, our research group demonstrated that this segment has an alternative DNA structure that could be involved in DNA duplication and breakage for the establishment of this mutation (Barbosa et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Sequence analysis showed that this intron has several conserved regions, mainly in the segment involved in the Nd-s D mutation in the fib-L gene. Recently, our research group demonstrated that this segment has an alternative DNA structure that could be involved in DNA duplication and breakage for the establishment of this mutation (Barbosa et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Genomic DNA from the C24A and M11A strains was extracted from the silk glands of 5-day-old fifth-instar larvae using the protocol previously described by Mills and Goldsmith (2000) with modifications detailed in Barbosa et al (2008). The A3 actin first intron from both strains was amplified with primers that anneal to sequences in exon 1 and exon 2 (forward 5ꞌAGG TGG TGC TCG AAC AGT GC3ꞌ; reverse 5ꞌAAT TTG CCG CGT GGG TCA GT3ꞌ) of the B. mori actin gene sequence (GenBank U49854).…”
Section: Dna Samplementioning
confidence: 99%
“…A pool of first-instar larvae from both strains (M11A and C24A) were macerated with liquid nitrogen, and DNA was extracted as previously described (Barbosa et al, 2008(Barbosa et al, , 2009. DNA fragments were amplified using the primers described in the DNA sample section.…”
Section: Conformation-sensitive Gel Electrophoresis -Csgementioning
confidence: 99%
“…Flanking sequences around the phased AT tracts and in CA n T motifs may also contribute to DNA conformation (Calladine et al 2004). These structures have been proposed to play a role in segments involved in the initiation of replication (Biamonti et al 2003;Altman and Fanning 2004;Fiorini et al 2006a), and they also seem to be structurally relevant for transcription (Fiorini et al 2001;Ohyama 2005;Gouveia et al 2008), nucleosome formation (Virstedt et al 2004), recombination events (Iarovaia et al 2004; Barbosa et al 2008), and fragile sites (Palin et al 1998). Furthermore, these structures have been found in Matrix Associated Regions (MARs) and replication origins (Anderson 1986;Krajewski and Razin 1992;reviewed in Fiorini et al 2006b).…”
Section: Introductionmentioning
confidence: 97%